Pakistan At the Crossroads : Domestic Dynamics And External Pressure - Jaffrelot, Christophe (New York Columbia University Press, 2017)
Top international scholars assess Pakistan's politics and economics and the challenges faced by its civil and military regimes. Contributors examine the state's handling of internal threats, tensions among political parties, police and law-enforcement reform, trends in judicial activism, the rise of border conflicts, financial entanglements with foreign powers, and diplomatic relations with India, China, Afghanistan, and the United States
Include Index
Keywords: Diplomatic relations -- Pakistan